Peripheral metabolic state and immune system in first-episode psychosis – A gene expression study with a prospective one-year follow-up. (May 2021) - Linnaranta, Outi; Trontti, Kalevi T.; Honkanen, Jarno; Hovatta, Iiris; Keinänen, Jaakko; Suvisaari, Jaana
Abstract: The excess availability of glucose and lipids can also have an impact on the dynamics of activation and regulation of peripheral immune cells. We aimed at understanding the correlations between peripheral metabolic state and immune system during the first year in first-episode psychosis (FEP). Patients with FEP (n = 67) and matched controls (n = 38), aged 18–40 years, were met at baseline, 2 and 12 months. Fasting peripheral blood samples were collected. We applied the NanoString nCounter in-solution hybridization technology to determine gene expression levels of 178 candidate genes reflecting activation of the immune system. Serum triglycerides, high-density lipoprotein (HDL), low-density lipoprotein (LDL) cholesterol and insulin and plasma glucose (fP-Gluc) were measured. We applied Ingenuity Pathway Analysis (IPA) to visualize enrichment of genes to functional classes. Strength of positive or negative regulation of the disease and functional pathways was deduced from IPA activation Z-score at the three evaluation points. We correlated gene expression with plasma glucose, triglycerids and HDL and LDL, and used hierarchical clustering of the pairwise correlations to identify groups of genes with similar correlation patterns with metabolic markers. In patients, initially, genes associated with the innate immune system response pathways were upregulated, which decreased by 12 months. Furthermore, genes associated with apoptosis and T cell death were downregulated, and genes associated with lipid metabolism were increasingly downregulated by 12 months. The immune activation was thus an acute phase during illness onset. At baseline, after controlling for multiple testing, 31/178 genes correlated positively with fasting glucose levels, and 54/178 genes negatively with triglycerides in patients only. The gene clusters showed patterns of correlations with metabolic markers over time. The results suggest a functional link between peripheral immune system and metabolic state in FEP. Metabolic factors may have had an influence on the initial activation of the innate immune system. Future work is necessary to understand the role of metabolic state in the regulation of immune response in the early phases of psychosis. Highlights: High-quality laboratory analysis with a medium-throughput technology for mRNA. A comprehensive and representative set of inflammatory markers. Peripheral immune system and metabolic state are functionally associated in first episode psychosis.